Gender Inequality in Education and Regional Economic Growth in Indonesia - Arifatul Karimah; Hera Susanti (Jurnal Ekonomi Pembangunan, 2022)
Gender equality, particularly in the areas of education, health, and employment, also serves as a stimulant for faster growth. In Indonesia, attempts to integrate gender equality into development are yielding positive outcomes, with national gender equality indicators improving. However, Indonesia's global standing remains poor, as judged by the Woman, Business, and Law (WBL) Index for 2021, which ranks it 149th out of 190 countries. To promote growth, initiatives to increase the number and quality of human resources, including providing persons with the chance to obtain the broadest possible education, are continuing. This study explores the attainment of gender equality in education, as well as how it relates to economic growth as a metric of progress, using district/city fixed effect panel data for the period 2011-2020.The study's findings show that during the observation period, there was still a gender gap in educational achievement, particularly outside of the Java-Bali region. Increasing gender equality through the ratio of women's years of schooling, as well as the ratio of women to the workforce with a junior high school education that is in line with the needs of the workforce, especially in the industrial sector, contributes positively and significantly to regional economic growth.